NON-PHARMACOLOGICAL INTERVENTIONS TO MANAGE DEMENTIA SYMPTOMS: A CLUSTER RANDOMIZED CONTROLLED TRIAL. (11th November 2018) - Tolea, M; Park, J; Rosenfeld, A; Arcay, V; Lopes, Y; Karson, J; Small, K; Galvin, J
Abstract: In a three-arm cluster-randomized trial, three community sites 1:1:1 were randomly assigned to Chair Yoga (CY), Participatory Music Intervention (PMI), or Chair-Based Exercise (CBE). Participants (10 in each group; 90% retention at the 6-week mark) attended twice-weekly 45-minute sessions for 12 weeks and were compared on physical function, psychological and behavioral symptoms, quality of life, and sleep quality. More participants were male (60%) and non-Hispanic White (77%); mean age was 84.6 years (SD = 7.7). A majority were diagnosed with Alzheimer's disease. Demographic and health information was collected and standardized assessment measures were administered. An intent-to-treat approach was employed in data analysis. Repeated-measures modeling was performed to examine group differences between baseline and 6-weeks (mid-intervention). Better physical performance at baseline (Mean mini-PPT= 7.70 ± 3.83SD vs. 5.10 ± 4.20SD) and a slight improvement by 6 weeks (Est. for time*CY: 1.04 ± 0.30, p=0.303) were observed in the CY group compared to the PMI group. Results were consistent across different measures of physical functionality. The CBE group performed similarly to the PMI group on physical functioning. A tendency for improvement in psychological symptoms (Est. time*CY term=-2.40 ± 0.65, p=0.015 for depression), quality of life (Est. time*CY term= 2.82 ± 1.97, p=0.167), and day sleepiness (Est. time*CY term.=-0.43 ± 1.57, p=0.771) was observed for the CY group. The other two groups experienced declines in these parameters. While the small sample limited the power to detect significant between-group differences, there was evidence of a positive effect of the CY intervention on physical functionality, quality of life, and dementia-related psychological and behavior symptoms.